Preliminary survey of araceae of Sg. Rawog conservation Area, Segaliud Lokan forest researve (FMU 19B) - Kartini Saibeh; S. Salleh (Sabah Forestry Department, 2019)
Considering that Sg. Rawog Conservation Area has been logged, it was thus with considerable surprise that the author encountered Rhaphidophora fluminea Ridl. along the river bank of Sg. Rawog since its first collection in 1897 from Bonggaya. Homalomena gempal Kartini, P.C Boyce and W.S Yeng was found growing on the sandstone of the river bank. Two interesting species of Schismatoglottis belong to the Trifiscata Complex were found not far from river bank of Trail 11. Alocasia princeps W. Bull and A. sarawakensis M. Hotta were found inside the forest at all trails except in the heath forest (Trail C49). Aroids climbers, namely Amydrium medium (Zoll. & Moritzi) Nicolson, Pothos sp., Rhaphidophora lativeginata M. Hotta, Scindapsus pictus Hassk. and Scindapsus sp. were found scattered in the inner area of the forest. In conclusion, the area around the river bank of Sg. Rawog represented aroid species found in pristine forest.